SOCIAL INTERACTION ABILITIES OF CHILDREN ON THE AUTISM SPECTRUM: A STUDY FROM THE PERSPECTIVE OF EDUCATIONAL PSYCHOLOGY - Alda Zahara Islamyati (CV. RADJA PUBLIKA, 2025)
Social skills are a fundamental aspect of child development, particularly for children on the autism spectrum (ASD). Children with autism often experience difficulties in social interaction, communication, and building relationships with peers and their environment. Educational psychology views social skills not only as a result of individual development, but also as influenced by the interaction between cognitive, affective, and environmental factors. This article aims to analyze the social skills of children on the autism spectrum from an educational psychology perspective, reviewing influencing factors, intervention strategies, and the role of inclusive schools. This literature review shows that the social skills of children with autism can be developed through psychopedagogical interventions, life skills-based learning , the use of interactive social media, and support for an inclusive educational environment. These findings emphasize that the roles of teachers, parents, and special education personnel are key in optimizing the social skills of children on the autism spectrum.